Ontologies in Knowledge Organization - Machado, Luís Miguel Oliveira (2021)
Definition: Within the knowledge organization systems (KOS) set, the term “ontology” is paradigmatic of the terminological ambiguity in different typologies. Contributing to this situation is the indiscriminate association of the term “ontology”, both as a specific type of KOS and as a process of categorization, due to the interdisciplinary use of the term with different meanings. We present a systematization of the perspectives of different authors of ontologies, as representational artifacts, seeking to contribute to terminological clarification. Focusing the analysis on the intention, semantics and modulation of ontologies, it was possible to notice two broad perspectives regarding ontologies as artifacts that coexist in the knowledge organization systems spectrum. We have ontologies viewed, on the one hand, as an evolution in terms of complexity of traditional conceptual systems, and on the other hand, as a system that organizes ontological rather than epistemological knowledge. The focus of ontological analysis is the item to model and not the intentions that motivate the construction of the system.